Urban agriculture as ecosystem services provider: A review - Fauzia, Assyifa; Frimawaty, Evi; Arifin, Hadi Susilo (Holistic: Journal of Tropical Agriculture Sciences, 2024)
Background: Urban agriculture’s role in mitigating the urban environment deterioration as ecosystem services provider. Urban agriculture adds various functions to different landscape scales, providing numerous benefits if managed correctly. This paper aims to study the role of urban agriculture as ecosystem services provider in mitigating urban environment deterioration. Method: The method that will be used in this article is literature review from articles related to urban agriculture and ecosystem services from provisioning, regulating, services, and culture. The review is compiled from urban agriculture’s function as ecosystem services provider, such as biodiversity conservation, microclimate regulation, aesthetic function, and food production. Result: In essence, urban agriculture is a diverse and vital solution for cities, and it takes various forms, from private gardens to community plots, addressing challenges like limited public funding and promoting greening initiatives. Urban agriculture plays a key role in biodiversity conservation, contributing to enhanced environmental benefits and the preservation of local habitats. Another crucial role in regulating the complex dynamics of the urban microclimate, offering ecological benefits such as reduced Urban Heat Island effects, wind protection, and pollutant absorption. Beyond its ecological impact, urban agriculture adds aesthetic value to urban spaces, creating visually appealing landscapes and promoting cultural integration. Moreover, it serves as a multifaceted strategy for sustainable urban development, addressing food security, resilience, and well-being. Conclusion: Amidst challenges, such as the threat to urban biodiversity and the need for proper green space management, urban agriculture emerges as a holistic approach, contributing to the visual, cultural, and environmental fabric of cities. Novelty/Originality of this article: This study offers a new perspective on urban agriculture as a multifunctional solution to address urban environmental degradation. By integrating agriculture into the urban landscape, the study reveals the transformative potential for creating greener, more resilient and sustainable cities.